La Gimnasia Artística con Intervención en niños con Hiperactividad - Andrade Hermida, Cesar David (2023)
The research entitled "Artistic Gymnastics as a means of intervention in children with hyperactivity", aims to determine how artistic gymnastics intervenes in children with possible hyperactivity, for which an exercise program focused on artistic gymnastics was applied to 11 children in the age range of 6 to 8 years from the FLY-GYM academy in the city of Riobamba. When talking about the methodological part, it has a type of critical-propositive research, a quasi-experimental design and a quantitative approach to obtain data from children who present signs of hyperactivity, while the Conners Test was used for data collection. , an abbreviated version in which parents and teachers are evaluated. Therefore, a program with a duration of 12 weeks with 3 training sessions per week was applied, each work session is focused on the adaptation of body movements for the improvement of basic gymnastic skills of children. Therefore, after the application of the program, results were obtained that it is verified that the practice of artistic gymnastics reduces the levels of hyperactivity. Finally, a notable change in the hyperactivity index was evidenced, with the exercise program it is possible to demonstrate how the practice of artistic gymnastics through playful games, recreational physical activities and scheduled training help to improve concentration, comprehension and thus improve the quality of life of the child.